Mechanical performance of epoxidized palm olein-epoxy coatings on metal surface / R. M. Taharim, Junaidah Jai and Najmiddin Yaakub - Taharim, R. M.; Jai, Junaidah; Yaakub, Najmiddin (2012)
Epoxy coatings are valued for their excellent adhesive strength and toughness, which are contributing factors in determining a coating life in aggressive environments. It has been shown in another study that epoxidized palm oil (EPO) can partially substitute diglycidyl ether of bisphenol A (DGEBA) in an epoxy coating formulation. Due to the presence of one epoxy ring per molecule of EPO, it is theorized that the cured EPO-DGEBA-amine network has a lower crosslinking density than a DGEBA-amine network, resulting in lower mechanical properties. However, it is expected that impact resistance would be enhanced due to the aliphatic chain present in EPO. This study aims to investigate the effect of EPO on the coating‟s adhesive strength and impact resistance. EPO-modified epoxy coatings were formulated using 30 wt% EPO in the resin system and cured using a cycloaliphatic amine adduct. Coatings were applied on mild steel specimens and heated to 100, 130 and 150oC for 90 minutes. Adhesion tests were done using the pull-off method and impact resistance tests were carried out using a falling dart of known weight from a fixed height. Test results showed that EPO-epoxy coating shows excellent adhesive strength and good impact strength when cured at 150oC for 90 minutes.